Evaluation of long‐term neurodevelopment in twin–twin transfusion syndrome after laser therapy. (15th November 2016) - Sananès, Nicolas; Gabriele, Victor; Weingertner, Anne Sophie; Ruano, Rodrigo; Sanz‐Cortes, Magdalena; Gaudineau, Adrien; Langer, Bruno; Nisand, Israël; Akladios, Chérif Youssef; Favre, Romain
Abstract: Objective: The primary objective of our study was to evaluate the long‐term neurodevelopment outcome after laser surgery for twin–twin transfusion syndrome (TTTS). The secondary objective was to identify perinatal prognostic factors associated with neurodevelopmental impairment. Method: This was a single‐center cohort prospective study carried out in pregnancies complicated by TTTS and treated by laser. Neurodevleopmental assesment included the administration of Ages and Stages Questionnaires® (ASQ), for the infants between 2 and 5 years of age. Results: A total of 187 patients underwent a laser for TTTS between 2004 and 2013. Significant brain lesions were detected in eight (2.9%) cases by ultrasound and/or magnetic resonance imaging including intraventricular hemorrhage, periventricular leukomalacia, and porencephaly. Questionnaires were administered to 126 children (50.4%) at 24 months or older at the moment of testing. There were 13.5% of those infants who had an abnormal ASQ (established as one area or more scoring < 2 SD) at 3.6 years ±1.3 follow‐up. There was a higher rate of abnormal ASQ among the infants with a birth weight below the fifth percentile ( p = 0.036). Conclusion: Twin–twin transfusion syndrome is associated with a risk of abnormal neurological development, even in case of laser surgery. Further studies are necessary to identify the risk factors for neurological impairment. © 2016 John Wiley & Sons, Ltd. Abstract : What's already none about this topic? Laser surgery improves neonatal survival and neurological outcomes in case of twin–twin transfusion syndrome (TTTS). There are only few studies on neurologic morbidity after laser, especially with a long‐term follow‐up setting. What does this study adds? This study shows that laser surgery in case of TTTS is associated with 13.5% of abnormal Ages and Stages Questionnaires at 3.6 years. It also suggests that a birth weight below the fifth percentile might be associated with neurodevelopmental abnormalities.